The ras responsive transcription factor RREB1 is a novel candidate gene for type 2 diabetes associated end-stage kidney disease - Bonomo, Jason A. (Hum Mol Genet, 2014)
Familial clustering and presumed genetic risk for type 2 diabetic (T2D) and non-diabetic end-stage kidney disease (ESKD) appear strong in African Americans. Examination of exome sequencing data in African American T2D-ESKD cases and non-diabetic non-nephropathy controls identified two low-frequency variants in the RREB1 gene, a repressor of the angiotensinogen (AGT) gene previously associated with kidney function, as being associated with T2D-ESKD: rs9379084 (P = 0.00087, OR = 0.26; D1171N) and rs41302867 (P = 0.00078, OR = 0.21; splice site variant). Rs41302867 replicated association in an independent sample of African Americans with T2D-ESKD [rs41302867 P = 0.033 (OR = 0.50)], and a trend towards rs9379084 association was observed (P = 0.070). In European Americans with T2D-ESKD compared with European American population based controls, both RREB1 variants replicated association [rs9379084 P = 1.67 × 10(−4) (OR = 0.54) and rs41302867 P = 0.013 (OR = 0.69)]. Rs9379084 was not associated with non-T2D-ESKD or T2D in African Americans (P = 0.55 and P = 0.37, respectively), but was associated with T2D in European Americans (P = 0.014, OR = 0.65). In African Americans, rs41302867 was associated with non-T2D-ESKD [P = 0.036 (OR = 0.54)] and hypertension attributed ESKD [H-ESKD, P = 0.029 (OR = 0.50)]. A meta-analysis combining African American and European American T2D-ESKD data revealed P = 3.52 × 10(−7) and 3.70 × 10(−5) for rs9379084 and rs41302867 association, respectfully. A locus-wide analysis evaluating putatively functional SNPs revealed several nominal associations with T2D-ESKD, non-T2D-ESKD and T2D in African and European Americans. RREB1 is a large, complex gene which codes a multidomain zinc finger binding protein and transcription factor. We posit that variants in RREB1 modulate seemingly disparate phenotypes (i.e. T2D, T2D-ESKD and non-T2D-ESKD) through altered activity resulting from splice site and missense variants.